Faktor Lingkungan, Motivasi, dan Beban Kerja dalam Loyalitas Karyawan - Nia Kurniati; Setyo Riyanto (Universitas Prasetiya Mulya, 2022)
This study aims to analyze and determine the effect of Work Environment, Work Motivation and Workload on Employee Loyalty at PT. Mowilex Indonesia. The population in this study were 310 employees of PT. Mowilex Indonesia. The sample used was 175 respondents, calculated based on the Slovin formula with a convenience sample technique. Methods of data collection using survey methods, with the research instrument is a questionnaire. Data analysis method used SPSS statistic 25 for descriptive analysis and Structural Equation Model with SmartPLS 3.0. This study proves that the work environment has a positive and significant effect on employee loyalty, work motivation has a positive and significant effect on employee loyalty, and workload has a positive and significant effect on employee loyalty.